2007
DOI: 10.1111/j.1460-9568.2007.05837.x
|View full text |Cite
|
Sign up to set email alerts
|

A spiking network model for passage‐of‐time representation in the cerebellum

Abstract: In Pavlovian delay eyeblink conditioning, the cerebellum represents the passage-of-time (POT) between onsets of conditioned and unconditioned stimuli (CS and US, respectively). To study possible computational mechanisms of the POT representation we built a large-scale spiking network model of the cerebellum. Consistent with our previous rate-coding model, we found two conditions necessary for the present model to represent the POT with a dynamic population of active granule cells: (i) long temporal integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(173 citation statements)
references
References 92 publications
7
165
1
Order By: Relevance
“…The emergence of the synchronized oscillation in the grcs and Gocs is consistent with the findings of Maex and De Schutter [7]. For the successive 2 s, in which a large current was injected to the grcs, the model grcs exhibited random alternation between burst and silent modes, consistent with the findings of Yamazaki and Tanaka [3]. After the current amplitude was decreased to that for the first 2 s, the network quickly returned to the oscillatory state at 9 Hz.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The emergence of the synchronized oscillation in the grcs and Gocs is consistent with the findings of Maex and De Schutter [7]. For the successive 2 s, in which a large current was injected to the grcs, the model grcs exhibited random alternation between burst and silent modes, consistent with the findings of Yamazaki and Tanaka [3]. After the current amplitude was decreased to that for the first 2 s, the network quickly returned to the oscillatory state at 9 Hz.…”
Section: Resultssupporting
confidence: 88%
“… monotonically decreased as | τ | increased with the POT-representation index PI  = 0.923. This indicates that the population of active grcs changed gradually with time from the onset of a large current injection without the recurrence of active grc populations, as reported by Yamazaki and Tanaka [3]. The NAC ( τ ) and for model Gocs were similar to those for model grcs (Fig.…”
Section: Resultssupporting
confidence: 83%
“…In our previous modeling study [25], we reported that such a sequence could be generated in response to sustained MF inputs in which the firing rate is constant at 30 spikes/s. In the present study, we suggested that a similar sequence can be generated even for the sinusoidally oscillating MF inputs at 0.5 Hz (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, the cerebellar VPFL is a strong candidate for the neural controller of our model. More specifically, we can consider the neural delay line structure as a model of the granular layer and the read-out neuron as a P-cell, in accordance with the cerebellar models which assume the granular layer as a basis for the spatio-temporal representation of the input signals and the P-cell layer as a layer that receives weighted projections from the granular layer [26] [27].…”
Section: Oculomotor Plant Modelmentioning
confidence: 99%